Phox2b-expressing retrotrapezoid neurons and the integration of central and peripheral chemosensory control of breathing in conscious rats - Takakura, Ana C.; Barna, Barbara F.; Cruz, Josiane C.; Colombari, Eduardo [UNESP]; Moreira, Thiago S. (Wiley-Blackwell, 2014)
New Findings What is the central question of this study? This study was designed to investigate whether the Phox2b-expressing neurons in the retrotrapezoid nucleus are important to breathing and chemoreflexes in conscious rats. What is the main finding and its importance? The high rate of destruction of a defined cell population (Phox2b(+)TH(-)) of the retrotrapezoid nucleus by the toxin suggests that the specialized connectivity of retrotrapezoid nucleus neurons, their glutamatergic nature and their relatively high sensitivity to CO2 are determinant factors in explaining their large contribution to the central and peripheral chemoreflexes.Chemoreception is the classic mechanism by which the brain regulates breathing in response to changes in tissue CO2/H+. A brainstem region called the retrotrapezoid nucleus (RTN) contains a population of Phox2b-expressing glutamatergic neurons that appear to function as important chemoreceptors. In the present study, we ask whether the destruction of a type of pH-sensitive interneuron that expresses the transcription factor Phox2b and is non-catecholaminergic (Phox2b(+)TH(-)) could affect breathing in conscious adult rats. The injection of substanceP (1nmol in a volume of 50nl) into the RTN increased respiratory frequency, tidal volume, minute ventilation and mean arterial pressure. Bilateral injections of the toxin substanceP conjugated with saporin (SSP-SAP) into the RTN destroyed Phox2b(+)TH(-) neurons but spared facial motoneurons, catecholaminergic and serotonergic neurons and the ventral respiratory column caudal to the facial motor nucleus. Bilateral inhibition of RTN neurons with SSP-SAP (0.6ng in 30nl) reduced resting ventilation and the increase in ventilation produced by hypercapnia (7% CO2) in conscious rats with or without peripheral chemoreceptors. In anaesthetized rats with bilateral lesions of around 90% of the Phox2b(+)TH(-) neurons, acute activation of the Botzinger complex, the pre-Botzinger complex or the rostral ventral respiratory group with NMDA (5pmol in 50nl) elicited normal cardiorespiratory output. In conclusion, the destruction of the Phox2b(+)TH(-) neurons is a plausible cause of the respiratory deficits observed after injection of SSP-SAP into the RTN. Our results also suggest that RTN neurons activate facilitatory mechanisms important to the control of breathing in resting or hypercapnic conditions in conscious adult rats.